Carrots and sticks : unlock the power of incentives to get things done - Ayres, Ian. (New York : Bantam Books, 2010)
The part-owner of StickK.com uses research into incentives and punishments to introduce the concept of "commitment contracts," an easy strategy for setting and achieving goals that is already in use by successful companies and individuals across America.
Includes bibliographical references and index.
rua 31/10/13
Loans
Keywords: Commitment (Psychology); Incentive (Psychology); Motivation (Psychology); Economics